Pengaruh Variasi Sudut Kampuh dan Kuat Arus Pengelasan Hasil Las SMAW Baja SS400 untuk Bahan Bejana Tekan terhadap Kekuatan Tarik dan Kekerasan - Hanan Setia Abadi; Subagiyo, Subagiyo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
A pressure vessel is a closed container that stores pressurized liquids or gases. Low-carbon steel is used as a material for pressure vessels that operate at low to moderate temperatures. One of the important aspects of manufacturing pressure vessels is the welding process. The welded area tends to be the weakest point due to exposure to high heat, which can lead to greater residual stress and potentially cause cracking. This study aims to evaluate the effect of variation in ample angle and current strength on mechanical properties, especially tensile strength, and hardness, to determine the optimal amplitude angle and current strength. The research method applied is an experiment by conducting SMAW welding on SS400 steel using E7016 electrodes, with a single V ample angle variation of 55°, 60°, 65°, and strong welding current of 110 A, 120 A, and 130 A, then a tensile test and hardness test are carried out. The results show that the tensile strength of the raw material is 481.2 with a hardness of 191.95 HVN. For the variation of the amputation angle, the highest tensile strength value was recorded at an angle of 55°, which was 567.471 N/mm2 , while the lowest was at an angle of 65°, which was 559.997 N/mm2 . The highest hardness value at a 65° angle reached 328.422 HVN, while the lowest at a 55° angle was 312.878 HVN. In terms of current strength variation, the highest tensile strength is obtained at 130 A which is 568.421 N/mm2 and the lowest at 110 A is 552.339 N/mm2 . The highest hardness value is found at a current strength of 110 A, which is 343.411 HVN, and the lowest at a current strength of 130 A, which is 295.122 HVN. The optimal parameters were found at a yield angle of 55° with a tensile strength of 567.471 N/mm2 and a hardness of 312.8 HVN and a current strength of 130 A with a tensile strength of 568.421 N/mm2 and a hardness of 295.1 HVN.